Integrating Generative AI into Non-Invasive Genetic Testing: Enhancing Early Detection and Risk Assessment - Sambasiva Rao Suura (Utilitas Mathematica, 2024)
This essay investigates the integration of Generative Artificial Intelligence (AI) with Non-Invasive Genetic Testing (NGT) to enhance early detection and risk assessment in genetic conditions. This research is motivated by the growing availability and decreasing costs of early-detection genetic tests which have potential benefits for individuals as well as in societal and health care systems. However, the increasing number of simple-to-use genetic testing kits also raises concerns about unassisted risk assessment as well as ethical, legal or social issues. Utilizing Generative AI systems can automatically create artificial data, enabling innovation and scientific progress so findings are strongly valued, as a significant part of both benefits and limitations could be universal for all kinds of genetic conditions. Hence, a comprehensive exploration is applied through desk research including a literature review capturing the current state of the art in genetic conditions, and primary research adding to it two N-of-1 case studies in connection with generative AI methods on primary genetic tests. The findings and contributions of this paper consist of several parts. Importantly, original content is generated using Generative AI about how the National Health System (NHS) can safely implement a two-step case-finding approach ensuring feasible cost-effectiveness, allowing a robust early detection system. The generated content is then enriched providing insights into family planning services and how the widespread utilization of a currently optional second genetic test would be ensured. The model described for a genetic condition review through desk research using the example of the currently most common genetic condition in the UK, Down Syndrome, is assumed to be newly developed. A systematic analysis is conducted on a potential beneficial framework summarizing how Generative AI could be utilized for both stratifying the risk and raising awareness about the limitations of genetic tests. Likewise, a vision is presented with case studies, DGene and EGene, showcasing the utility of Generative AI with Genetic Models. This point is original and includes insights on the idea itself and how Generative AI is planned to be used as well as alignment to past experiences and study guidelines. The case studies, the described Genetic Models, and the Gamete Study are also original works with potential benefits for similar future disputes. Because the integration of Generative AI into NGT would be dipping a toe into novel scientific territory and could have potential revolutionary impacts, it also discusses concerns, contentious points, and other implications.